Financial safety nets in Asia: Genesis, evolution, adequacy, and way forward - Hal Hill; Jayant Menon (Asian Development Bank Institute (ADBI), 2012)
Financial safety nets in Asia have come a long way since the Asian Financial Crisis (AFC) of 1997 - 98. Not wanting to rely solely on the International Monetary Fund (IMF) again, the Chiang Mai Initiative (CMI) was created in 2000. When the CMI also proved inadequate following the Global Financial Crisis (GFC), it was first multilateralized (CMIM), and then doubled in size to 240 billion, while the IMF de-linked portion was increased to 30%. A surveillance unit, the Association for Southeast Asian Nations (ASEAN)+3 Macroeconomic Research Office (AMRO), was set-up in 2011. These are impressive developments, but are they enough to make the CMIM workable? Without clear and rapid-response procedures to handle a fast-developing financial emergency, it is unlikely that the CMIM will be used even as a complement to the IMF. To serve as a stand-alone option however, its size or the IMF de-linked portion of funds needs to be further increased, as does its membership to add diversity. But if AMRO could develop into an independent and credible surveillance authority, then it could lead the next rescue.
Keywords: F32; F33; F34; 330; financial safety nets; chiang mai initiative; asean+3; asia; asian monetary fund; imf; Finanzkrise; Finanzmarktregulierung; Asien